Realia to improve vocabulary among students of seventh grade at escuela de educación básica Rosendo Félix Mejillón, La Libertad, province of Santa Elena. school year 2015-2016. - Ponce Hermenejildo, Katiuska Lilibeth (2016)
This research paper emphasizes vocabulary one the most important aspects when the English language is learned. The use of authentic materials or real items at the moment to teach vocabulary in the English classes is the best way to acquire new word for students. It is suggested that due to the educative requirement, this proposal be implemented since students feel motivated to develop their English communicative skills focused in vocabulary. The use of realia is an appropriate method to improve vocabulary applying didactic resources. For the development of this investigation the qualitative and quantitative method were applied. As techniques applied in it, focus group and interviews were put in practice. All the information was analyzed carefully at the moment to show the results. This research work was implemented at escuela de educación básica Rosendo Félix Mejillón among students of seventh grade. The designed proposal used realia activities in the teaching-learning process to acquire vocabulary in the English language. The results show that students highly increase their vocabulary, it means that the use of Realia resources as an English teaching technique in the teaching learning process is the one of best way to improve the students ‘vocabulary.